Social processes in children's learning - Light, Paul (Cambridge studies in cognitive perceptual development, 1999)
"This book is about children's learning and problem-solving behaviour. It reflects the increasingly close integration seen in recent years between social and cognitive approaches to researching the learning process. In particular, Paul Light and Karen Littleton examine the ways in which interactions between children influence learning outcomes." "This book will be a valuable tool for researchers, teachers and practitioners interested in the social processes of children's learning."--Jacket